Desired Characteristics of Educational Institution Administrators Under The Jurisdiction of the Primary Educational Service Area Office in Lopburi Province - Sommit, Winai; Sriruksa, Pratoom; Toonthong, Songsri; Pachanavon, Apison (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This research article aims to study and compare the desired characteristics of educational institution administrators under the jurisdiction of the Primary Educational Service Area Office in Lopburi Province, classified by gender, work experience, job position and size of the institution. The sample group used included 66 educational institution administrators and 263 teachers in the academic year 2023, totaling 329 people from stratified random sampling, according to the size of the educational institution. The instrument used in this research was a questionnaire. The reliability value was 0.937. Data were analyzed by using percentage, mean, standard deviation, t-test one-way analysis of variance and pairwise tests according to Scheffe's method. The research results found that 1. Desired characteristics of educational institution administrators overall and each aspect were at a high level, which was sorted average values from highest to lowest were as follows: responsibility, being an efficient person, decision-making, motivation, and human relations and 2. Results of the comparison of desirable characteristics of educational institution administrators under the jurisdiction of the Primary Educational Service Area Office in Lopburi province when classified according to the size of the educational institution, it was found that the views of the administrators and teachers were different at a statistical significance .05. When classified by gender, work experience, and job position, there were no differences in their views.